2018
DOI: 10.1007/s00431-018-3221-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin as predictor of acute kidney injury in neonates with perinatal asphyxia: a systematic review and meta-analysis

Abstract: Serum and urinary NGAL represent candidate biomarkers with high performance in the prediction of acute kidney injury in newborns with perinatal asphyxia. Before NGAL can be widely used in clinical practice, future large prospective studies are needed to define the optimal cutoffs and accurately determine which levels are suggestive of post-asphyxial acute kidney injury. What is Known: • Acute kidney injury is a major cause of morbidity and mortality in perinatal asphyxia. • Current markers are insufficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…AKI biomarkers in the urine have been shown to be predictive of AKI and mortality in children undergoing cardiopulmonary bypass [12] and in critically ill preterm infants [13]. Urinary neutrophil gelatinase-associated lipocalin (NGAL) has bacteriostatic properties and contributes to innate immunity [14]. At the early phase of ischemia-induced AKI there is a rapid upregulation of NGAL mRNA in the Henle loop and proximal tubules, causing an increase in the synthesis and excretion of NGAL into the urine.…”
Section: Introductionmentioning
confidence: 99%
“…AKI biomarkers in the urine have been shown to be predictive of AKI and mortality in children undergoing cardiopulmonary bypass [12] and in critically ill preterm infants [13]. Urinary neutrophil gelatinase-associated lipocalin (NGAL) has bacteriostatic properties and contributes to innate immunity [14]. At the early phase of ischemia-induced AKI there is a rapid upregulation of NGAL mRNA in the Henle loop and proximal tubules, causing an increase in the synthesis and excretion of NGAL into the urine.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies described a correlation between uNGAL values and the severity of sepsis and asphyxia, even in the absence of associated AKI. Studies also describe a positive correlation between uNGAL values and inflammatory markers like C-reactive protein and procalcitonin [14,21]. Currently, uNGAL production associated with tubular injury (as a monomer) or with inflammatory or ischemic processes (as a dimer) cannot be technically differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…NGAL is a newly identified adipokine that is highly expressed in cells from various pathological tissues with abnormal metabolism [39,40]. Many studies have shown that NGAL has a rapid elevation at blood levels during kidney injury, and its sensitivity for ischemic or nephrotoxic AKI is significantly higher than P r e p r i n t traditional kidney injury markers such as SCr and SUr [35,41,42]. Since its recommendation by the US FDA as a marker of renal function in 2002, CysC has been widely used in clinical applications because it is not affected by factors such as age, gender, and body weight inflammation.…”
Section: P R E P R I N Tmentioning
confidence: 99%